Project-based learning innovation through animated learning videos to sharpen students’ creativity and understanding - Elisma Elisma; Nurul Kamilah Sadli; Syamsurizal Syamsurizal (Jurnal Inovasi dan Teknologi Pembelajaran, 2025)
The learning paradigm has shifted from Teacher-Centred Learning (TCL) to Student-Centred Learning (SCL), emphasizing active students’ participation to increase their understanding, creativity, and skills in facing professional challenges. One method that supports this approach is Project-Based Learning (PjBL) combined with Animated Learning Video (ALV). This method is applied to help students understand biochemistry courses, which are often considered challenging. This research adopted a pre-experimental design to measure the increase in students’ understanding through pre-tests and post-tests after implementing the learning method. This research involved two classes with 64 students using total sampling techniques. The research results show that applying the ALV-based PjBL method is practical in increasing students’ understanding, as evidenced by a higher average score compared to conventional methods and improving students’ satisfaction in studying biochemistry. However, applying this method requires repetition and collaboration with other methods to deepen students' memory.